The National Network for Educational Renewal and the Legacy of John Goodlad. (1st October 2016) - Michelli, Nicholas M.
Abstract: This article gives an overview of this themed issue of the Record, in which all the contributing authors report on their National Network for Educational Renewal settings, where students are educated to participate in a socially just democratic society .